Analisis Faktor Risiko Kejadian Ulkus Diabetik Pada Penyandang DM Tipe 2 - Eka Rahayuningsih; Haryani Haryani; Nanik Sri Kodriyati (Journal of Bionursing, 2026)
Background. Diabetic foot ulcers are a major complication of diabetes that cause increased morbidity and mortality and poor quality of life. Although there are many studies on risk factors for diabetic ulcers, only a few use a case-control design with age matching. Knowledge about this is important to increase awareness of early detection and prevention of diabetic ulcers. Methods. Quantitative case control study using a retrospective approach by identifying groups affected (cases) and not affected (controls) by matching age. Data using medical records from January 2023 to December 2023. The sample used was data from196 type 2 DM patients consisting of 98 diabetic ulcer patients and 98 patients without diabetic ulcers at the Endocrine Polyclinic of Dr. Sardjito Hospital. Data were analyzed using univariate, bivariate odds ratio analysis, and multivariat analysis with STATA application. Results. The prevalence of diabetic ulcers in people with type 2 DM in the Endocrine Clinic of Dr. Sardjito Hospital is 23%. The risk factors for long suffering from DM, hypertension, blood sugar control, neuropathy, and PAD have an OR value > 1. The risk factors for long suffering from DM, DM neuropathy, history of hypertension, and PAD have a p-value < 0.05. Conclusion. The prevalence of risk factors for diabetic ulcers in people with type 2 DM at the Endocrine Clinic of Dr. Sardjito Hospital is quite high. Risk factors for duration of DM, hypertension, blood sugar control, neuropathy, and PAD showed an increased risk. The risk factors of duration of DM, DM neuropathy, history of hypertension, and PAD significantly affect the incidence of diabetic ulcers in people with type 2 DM. Keywords Keywords: risk factors, diabetic ulcers, type 2 diabetes patients.